Cleat-surface Interface and Lower Extremity Injuries - Davie, Ryann; Ammerman, Brittany; Pahapill, Natalie; Sutton, Karen (Journal of Sports Medicine and Therapy, 2023)
Non-contact injuries with playing surfaces occurring from applied player impact and frictional forces are a major source of lower extremity injuries in competitive sports. Artificial playing surfaces are a common alternative to natural grass surfaces; however, these surfaces are associated with player injury as well. The purpose of this manuscript is to explore the existing literature on the relationship between cleat surface interface and lower extremity injuries in athletes and the importance of proper playing surface conditions alongside proper cleat selection to optimize injury prevention and athletic performance. As artificial turf has become more advanced, studies have shown the rates of lower extremity injuries of the knee, ankle, and foot have decreased to be more similar to the rate of injury on natural grass. However, foot and ankle injury rates remain significantly higher on artificial turf. Furthermore, certain studies continue to demonstrate an increased rate of knee injuries in football players, suggesting that significant performance differences still exist between artificial turf and natural grass. Future studies warrant focusing on ways to improve the cleat-surface interface of new-generation turf, emphasizing proper cleat selection, and playing surface conditions for injury prevention thus optimizing athletic performance.